Neck Kinematics in Patients With Chronic Mechanical Neck Pain: An Observational Study to Explore the Integration of Multiple Influencing Factors Through a Bayesian Model-Based Approach - Oscar Rodriguez Lopez; Filippo Moggioli; Elena Bocos Corredor; Constantino Antonio Garcia Martinez; Hector Beltran-Alacreu; Sonia Liebana Sanchez-Toscano; Cristina Sanchez Lopez de Pablo; Rafael Raya Lopez; Aitor Martin-Pintado Zugasti (IEEE, 2024)
The aim of this observational, cross-sectional study is to evaluate potential differences in kinematics, specifically range of motion (ROM) and velocity, during planar cervical movements between patients with non-traumatic chronic neck pain and disability and asymptomatic controls, while accounting for potential influencing variables of age, sex and fear of movement. The influence of pain intensity, neck disability, age, sex or fear of motion on kinematics was analyzed through robust multivariate Bayesian regression models fitted using the brms library in R. Forty-three patients with neck pain (aged 36.70 ± 13.75 years; 10 men and 33 women) and 42 asymptomatic participants (aged 32.74 ± 13.24 years; 25 men and 17 women) completed the study protocol. The presence of neck pain/disability was associated with lower ROM and peak velocity during all planar movements when considering the influence of age, sex or fear of motion, with standardized regression coefficients that had a small effect size (ranged from 0.11 to 0.28) and estimated differences of less than 2.21° in ROM and 25.61°/s in peak velocity. Although patients with chronic mechanical neck pain showed reduced ROM and peak velocity, the small effect sizes and the low estimated differences between groups question the relevance and clinical usefulness of kinematic analysis of planar movements in samples of patients similar to those included in our study. It is probable that there are differences between the groups, but it is insufficient to rely solely on kinematic variables for patient discrimination. This limitation likely arises from the substantial variability in patient kinematics.